Pro Eclipse JST: Plug-ins for J2EE Development - Judd, Christopher M. (Apress, 2012)
Developing enterprise Java applications using Java 2 Enterprise Edition (J2EE) is difficult enough. Developers need to use good integrated development environments (IDEs) and tools to simplify the complexity and increase developer productivity. The Eclipse Web Tools Platform (WTP) project is one such collection of tools. WTP is the first open source comprehensive collection of tools for building J2EE applications on top of the Eclipse Platform.